Atrophy of the brachialis muscle after a displaced clavicle fracture in an Ironman triathlete: case report - Rüst, Christoph Alexander; Knechtle, Beat; Knechtle, Patrizia; Rosemann, Thomas (Journal of Brachial Plexus and Peripheral Nerve Injury, 2011)
Clavicle fractures are frequent injuries in athletes and midshaft clavicle fractures in particular are well-known injuries in Ironman triathletes. In 2000, Auzou et al. described the mechanism leading to an isolated truncular paralysis of the musculocutaneous nerve after a shoulder trauma. It is well-known that nerve palsies can lead to an atrophy of the associated muscle if they persist for months or even longer. In this case report we describe a new case of an Ironman triathlete suffering from a persistent isolated atrophy of the brachialis muscle. The atrophy occurred following a displaced midshaft clavicle fracture acquiring while falling off his bike after hitting a duck during a competition.
Keywords: Displaced clavicle fracture; Ironman triathlete; muscular-atrophy; brachialis muscle; brachial plexus